2020
DOI: 10.2139/ssrn.3629666
|View full text |Cite
|
Sign up to set email alerts
|

Does Fake News Affect Voting Behaviour?

Abstract: Over the last decade, the erosion of trust in public institutions and traditional media sources have been proceeding in parallel. As recent developments in media consumption have led to a proliferation of politically charged online misinformation, it is no wonder that many have been questioning whether the spread of fake news has affected the results of recent elections, contributing to the growth of populist party platforms. In this work, we aim to quantify this impact by focusing on the causal effect of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 14 publications
0
21
0
Order By: Relevance
“…However, there are some studies that address the consumption and dissemination of fake news in the European context. The investigation has sought, above all, the influence of disinformation during the electoral campaigns of several countries, as in the debate related to Brexit [26], in the Italian general elections [27], in the French elections [28] or in the German elections [6] through the coordination of social bots on twitter. The impact that disinformation has on the European Union's unification policies has also been investigated [29], especially with regard to pro-Russian propaganda and the ultranationalist, xenophobic and antiimmigration populist rhetoric that discredits the European Union project [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are some studies that address the consumption and dissemination of fake news in the European context. The investigation has sought, above all, the influence of disinformation during the electoral campaigns of several countries, as in the debate related to Brexit [26], in the Italian general elections [27], in the French elections [28] or in the German elections [6] through the coordination of social bots on twitter. The impact that disinformation has on the European Union's unification policies has also been investigated [29], especially with regard to pro-Russian propaganda and the ultranationalist, xenophobic and antiimmigration populist rhetoric that discredits the European Union project [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…The impact that disinformation has on the European Union's unification policies has also been investigated [29], especially with regard to pro-Russian propaganda and the ultranationalist, xenophobic and antiimmigration populist rhetoric that discredits the European Union project [29][30][31]. As in the American scenario, some studies support the idea of very small audiences for fake news [27,32]. Our study adds to the current literature with a unique European perspective and could motivate future investigations in this area.…”
Section: Introductionmentioning
confidence: 99%
“…It is only in 2020, when we observe research based on 2018 election data, that we see a clear focus on fake news (Cantarella et al, 2020), disinformation (Pierri et al, 2020), and media manipulation (Giglietto et al, 2020).…”
Section: Ten Years Of Questionsmentioning
confidence: 92%
“…Phase III (2018-2020) shows a return of older features as well as the consolidation of new dynamics. In terms of research questions, the paper refocused their interest on the issue of populism, but especially after 2019, this focus was coupled with parallel issues that emerged in the international debate, such as fake news (Cantarella et al, 2020) and disinformation (Pierri, Antoni & Ceri, 2020). 2018 saw a slight increase in theoretical papers, characterized by a focus on populism and its international dimensions (Bickerton & Accetti, 2018;Chiaramonte et al, 2018).…”
Section: -2020: a New Landscapementioning
confidence: 99%
“…To the best of our knowledge, only two studies have explored the consequences of fake news on real-world behaviours, both by looking at geographical patterns. Cantarella et al (2019) used linguistic differences in South Tyrol in Italy to estimate how much misinformation specific geographical areas received and whether it led to populist voting. They concluded that fake news did not significantly affect group-level voting behaviours.…”
Section: Measuring the Effects Of Misinformation On Behavioursmentioning
confidence: 99%